A execução penal alternativa no Brasil: paradigma de prevenção criminal e de proteção de direitos - Roessing, Telma de Verçosa (2011)
This master s dissertation aims to investigate how alternative sanctions are enforce in Brazil in order to identify if this practice constitutes a model for preventing criminal recurrence and protecting the fundamental rights of persons who have been sanctioned due to low and medium gravity crimes. The research starts by analyzing the State punitive power through the point of view of the Democratic State under the Rule of Law and the penalty principles in the Brazilian Constitution, situating the alternative sanctions and measures within the minimalist approach of Criminal Law. Subsequently it analyzes the public policies which approach the public security problem in a broader way, focusing mainly in the criminality prevention, and also points out the pendular character of Brazilian criminal law, which moves between greater and lesser strictness. Further on, it highlights the failure of imprisonment, and the alternative sanctions are presented as criminal sanctions with an educational and reintegrating character. From the treatment provided to alternative sanctions and measures in the United Nations Standard Minimum Rules for Non-custodial Measures (The Tokyo Rules), the research emphasizes the alternative sanctions and measures in the Brazilian legislation and analyzes such alternatives as an interaction process between the State, the community and individuals. Furthermore, it stresses the course taken by the Brazilian experience in the implementation of public policies aimed at the enforcement of alternative sanctions, highlighting the Alternative Sanctions and Measures Incentive Program from the Brazilian Ministry of Justice (Programa de Fomento às Penas e Medidas Alternativas do Ministério da Justiça). The sustainability of the support policy to alternative sanctions and measures in the states, taking into account experiences in several ones, is also analyzed, as well as the proposal for a public security policy with citizenship in the enforcement of alternative sanctions and measures; last, but not least, this research also evidences the possibility of structuring an autonomous alternative criminal justice system in the country.